2018
DOI: 10.4244/eij-d-17-00550
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of the PRECISE-DAPT and PARIS risk scores for predicting one-year out-of-hospital bleeding in acute coronary syndrome patients

Abstract: Within our cohort, PARIS and PRECISE-DAPT were fairly to moderately effective for the prediction of bleeding. Their predictiveness varies according to the bleeding severity. PARIS-derived bleeding risk assessment was associated with a higher net benefit compared to PRECISE-DAPT-based bleeding risk assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 19 publications
1
20
1
2
Order By: Relevance
“…17 The rate of anaemia was 16% in the Cardiología del Complejo Hospitalario Universitario de VIgo (CardioCHUVI) PCI registry, while its prevalence in our study was 32.3%. 18 Moreover, anaemia was significantly more common in the female patients in our study than in the male patients. The particular presence of anaemia among the female patients may explain the high PRECISE-DAPT scores observed in these patients in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…17 The rate of anaemia was 16% in the Cardiología del Complejo Hospitalario Universitario de VIgo (CardioCHUVI) PCI registry, while its prevalence in our study was 32.3%. 18 Moreover, anaemia was significantly more common in the female patients in our study than in the male patients. The particular presence of anaemia among the female patients may explain the high PRECISE-DAPT scores observed in these patients in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…In the Spanish CardioCHUVI (Cardiologia del Complejo Hospitalario Universitario de Vigo) cohort (n=1,926),PARIS bleeding score and PRECISE-DAPT score were retrospectively validated. 54 For major bleedings, PARIS and PRECISE-DAPT showed a moderate discriminative power and, using decision curve analyses, it was concluded that the PARIS bleeding score had a superior performance. Recently, the DAPT score was successfully validated in a pooled Japanese cohort (n=12,223).…”
Section: Patient-tailored Duration Of Dual Antiplatelet Therapymentioning
confidence: 99%
“…Notably, these high-risk features are well recognized to predispose to higher rates of thrombotic events [20][21][22], but they were the exclusion criteria in a retrospective analysis using the pooled patient-level data of 6 randomized controlled trials [7]. Validation of the PARIS bleeding score and instruction for its calculation were described elsewhere [16,18,23]. Patients were deemed at HBR for scores ≥8 and non-HBR for scores <8. e primary ischemic outcome was MACE, defined as a composite of cardiac death, MI, definite or probable ST, and target lesion revascularization (TLR).…”
Section: Definitions and Clinical Outcomesmentioning
confidence: 99%